2016
DOI: 10.1109/tase.2016.2605149
|View full text |Cite
|
Sign up to set email alerts
|

An MILP Optimization Problem for Sizing Port Rail Networks and Planning Shunting Operations in Container Terminals

Abstract: This paper proposes an optimization approach for sizing port rail networks and planning railway shunting operations by adopting a discrete-time model of the overall system. First, a mixed-integer linear mathematical programming problem is defined in order to optimize shunting operations to be performed on the considered network by satisfying certain arrivals and departures of import and export flows. Moreover, the proposed procedure can be used to evaluate the capacity of a port rail network, in terms of maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The queues' length is determined by the arrival rates, initial conditions, and service rate of terminal resources. Similar research can be found in Caballini et al [22] and Mishra et al [32].…”
Section: Methodologies and Eories Used In Port Itt Planningsupporting
confidence: 89%
See 2 more Smart Citations
“…The queues' length is determined by the arrival rates, initial conditions, and service rate of terminal resources. Similar research can be found in Caballini et al [22] and Mishra et al [32].…”
Section: Methodologies and Eories Used In Port Itt Planningsupporting
confidence: 89%
“…Several simplifications have been applied in modeling the ITT operations like container handling time, transport time, and costs. For example, the productivity of shunting yards could be hard to accurately estimate in Caballini et al [21], Caballini et al [22]; and Mishra et al [32] only consider homogeneous vehicle capacity and no congestion was taken into account. These simplifications and assumptions keep the problem solvable but may result in losing accuracy.…”
Section: Methodologies and Eories Used In Port Itt Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregate discrete-time models have already been used for performance evaluation and optimization of specific intermodal transportation processes. In [41], [42], for instance, discrete-time models for freight movements by rail in maritime terminals are described. The model presented in this section is much more extensive considering the movement not only of freight but also of passengers and considering a more general applicative context.…”
Section: The Intermodal Dynamic Model For Passenger and Freight Flowsmentioning
confidence: 99%
“…The scheduling of RSs, which are widely used in railway container terminals, has not been well studied. Moreover, the handling operation for sea–rail intermodal container transportations is scarcely studied, and existing research related to intermodal transportation has mainly focused on the coordination of different modes ( 21 ), network planning ( 22 ), and evaluation ( 23 ). Therefore, the integrated scheduling of the RMGs, RSs, and ITs in container terminals for sea–rail intermodal transportation is studied in this paper.…”
Section: Literature Reviewmentioning
confidence: 99%